Die Entwicklung der kurdischen Freiheitsbewegung : Gesammelte Texte zur Einführung in Geschichte und Gegenwart - Jongerden, Joost; Akkaya, Ahmet Hamdi (2022)
In this anthology, Joost Jongerden and Ahmet Hamdi Akkaya take a thorough and by no means uncritical look at the political project of the Kurdistan Workers' Party, the PKK. Quite in contrast to the study of the Kurdish question in Turkey, which has been taking place on a large scale for a long time, research on Kurdish organisations is rare. In particular, little attention has been paid to the PKK's understanding of politics, so this collection fills a research gap. The texts demonstrate that the idea of reshaping Kurdistan's society must be understood as a project of radical democracy and is not merely a localised initiative, but rather part of a larger idea.